Does overexertion correlate with increased injury? The relationship between player workload and soft tissue injury in professional American football players using wearable technology - Li, R. T.; Salata, M. J.; Rambhia, S.; Sheehan, J.; Voos, J. E. (Sports Health: A Multidisciplinary Approach, 2020)
Background: The relationship of training load to injury using wearable technology has not been investigated in professional American football players. The primary objective of this study was to determine the correlation between player workload and soft tissue injury over the course of a football season utilizing wearable global positioning system (GPS) technology.